Dream more : celebrate the dreamer in you - Parton, Dolly (G.P. Putnam's Sons, 2012)
Based on her popular commencement speech at the University of Tennessee and drawing on her own life experiences, the country superstar explores the four great hopes she urges everyone to embrace--dream more, learn more, care more, and be more.